Por uma política da voz no cinema: estratégias para a emancipação do espectador em memórias do subdesenvolvimento de Tomás Gutiérrez Alea - Döppenschmitt, Elen Cristina Souza Koch Vaz (2010)
We have analyzed the Cuban movie Memories of Underdevelopment (1968), by Tomás Gutiérres Alea, based on the homonymous novel by Edmundo Desnoes (1965) in an attempt to understand its revolutionary character. Throughout the study of the movie s critical fortune, we have found many works of historical perspective, whose analysis, though efficient in detailing the movie s context of production, repeat themselves when interpreting the aesthetical procedures in use. As for the revolutionary character, the concept was examined considering the historical frameworks, social temporalities and political specificities, putting the communicative mediations between public and means (Barbero, 2002) into evidence; for that, not only the movie, but also the author s theoretical essays and the analysis of his belonging to the Nuevo Cine Latinoamericano and the ICAIC were considered. As an act of translation of the literary work, we have understood that the movie amplify the meanings of the previous work and leaving concepts such as fidelity or original aside. We have tried to understand how the intertextuality and the dialogism present in the work operate through certain aesthetical strategies, so that a cultural interpretation of the work would be possible (Stam, 2008). It is through the complementarity of the aesthetical procedures used in each of the means of artistic expression (the self-referentiality in the novel and the collage in the movie) that we achieve a better understanding of what is encrypted in this narrative about the revolution, whose protagonist (writer) is the figuration of the intellectual who questions his role in face of the new reality. In the movie, the subjectivity of the narrative loses its legitimacy at the same time that other points of view are offered, making a new relation between spectacle and audience, by the means of the identification-distanciation game. Supported by Branigan (1984), to whom this game is understood by the modulation of the looks and voices which inform the reality, we have observed the ways in which the audience transits throughout the points of view of the character of the narrative authority. When emphasizing the role of the voice in the destabilization of the point of view , we have shown how the deconstruction of the voice-over s authority has taken place in the movie, by focusing on popular oral and media texts. For that, we have done a mapping of the voices in Memories in order to build analysis categories; those categories reflect the comparison with the main theories on the voice in the cinema, (CHION, DANEY, BONITZER, GODREAULT & JOST, METZ), as well as with the theories on orality. (ZUMTHOR, MESCHONNIC). Therefore, we have concluded that the uses of the voice (in, off, over, voix-je), the voice as sound landscape and voice texts (poems, songs, oratory ) are worked in order to potentialize the voice for political effects